End-to-end design of a competitive car with a high level of handling and safety indicators - N. A. Volkova; N. T. Katanaev; A. E. Chebyshev (Вестник университета, 2022)
The paper reveals the prospects for the development of end-to-end design when creating innovative automotive equipment with consumer properties that contribute to the successful promotion of the manufactured product in the market of goods and services. A description of the structure and functions of the system is given, which is based on the modeling of a human-machine system in order to obtain optimal indicators of consumer properties of the design object. A description of the methodology for determining the normalized indicators of consumer qualities using a database of 18 car brands, for which 15 expert assessments were obtained for each car. The differential and integral types of analysis used in the study make it possible to identify weaknesses and strengths for any brand of car. The research results are intended to create a car with the best handling and safety indicators, ensuring high competitiveness, which is very relevant in today’s realities. It should also be noted that this study of quality criteria can become the basis for the creation of innovative products in the automotive industry.